2008
DOI: 10.1111/j.1467-8624.2008.01149.x
|View full text |Cite
|
Sign up to set email alerts
|

Values as Protective Factors Against Violent Behavior in Jewish and Arab High Schools in Israel

Abstract: This study tested the hypothesis that values, abstract goals serving as guiding life principles, become relatively important predictors of adolescents' self-reported violent behavior in school environments in which violence is relatively common. The study employed a students-nested-in-schools design. Arab and Jewish adolescents (N = 907, M age = 16.8), attending 33 Israeli schools, reported their values and their own violent behavior. Power values correlated positively, and universalism and conformity correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
100
1
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(126 citation statements)
references
References 69 publications
13
100
1
7
Order By: Relevance
“…We trust that this goal has been achieved. In particular, we found that the values were predictors of typical bullying behavior, which is in agreement with the results found in previous studies (Knafo, 2003;Knafo et al, 2008;Menesini et al, 2013. ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We trust that this goal has been achieved. In particular, we found that the values were predictors of typical bullying behavior, which is in agreement with the results found in previous studies (Knafo, 2003;Knafo et al, 2008;Menesini et al, 2013. ).…”
Section: Discussionsupporting
confidence: 93%
“…In fact, these presumptive associations were found in studies using the Schwartz model (1992) in which a positive correlation of aggressive behavior among peers and self-enhancement values (power and achievement) were found; and negative correlation with self-transcendence (universalism and benevolence), which describes those who care about the well-being and interest of others (Benish-Weisman, 2015;Knafo, 2003;Knafo, Daniel, & Khoury-Kassabri, 2008;Menesini, Nocetini, & Camodeca, 2013).…”
Section: Values and Bullyingmentioning
confidence: 95%
“…Confi a-se que este objetivo tenha sido alcançado. Concretamente, foi possível verifi car que os valores foram preditores de comportamentos típicos do bullying, algo congruente com os resultados encontrados em estudos pré-vios (Knafo, 2003;Knafo et al, 2008;Menesini et al, 2013).…”
Section: Discussionunclassified
“…De fato, estas presumíveis associações foram verifi cadas em estudos utilizando o modelo de Schwartz (1992), quando se constatou correlação positiva do comportamento agressivo entre pares e os valores de autopromoção (poder e realização) e, em sentido oposto, com os de autotranscendência (universalismo e benevolên-cia), que descrevem aqueles que preocupam-se com o bem-estar e interesse dos demais (Benish--Weisman, 2015;Knafo, 2003;Knafo, Daniel, & Khoury-Kassabri, 2008;Menesini, Nocetini, & Camodeca, 2013).…”
unclassified
“…Logo, entende-se que a ética pressupõe uma ação reflexiva, na dimensão do querer, cujas decisões levam em conta a vida individual e o sentido atribuído pelo sujeito à vida em sociedade. Sendo assim, os valores morais podem ser considerados os investimentos que motivam o sujeito a comportar-se de certa maneira e o levam a julgar e justificar a sua própria ação e a dos outros (KNAFO; DANIEL; KHOURY-KASSABRI, 2008;SCHWARTZ, 1992). Segundo Piaget (1994), os valores são investimentos afetivos que movem o sujeito e guiam suas ações.…”
unclassified